ARTIFICIAL INTELLIGENCE AS A CATALYST FOR INNOVATION IN HIGHER EDUCATION - Kulmamatov Oybek Amonovich,; Ochildiyev Iskandar, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: This article explores the transformative impact of Artificial Intelligence (AI) on higher education, focusing on how AI-driven tools and systems improve learning efficiency, personalization, assessment methods, and academic administration. AI has emerged as a vital technological force, reshaping traditional educational models into more dynamic, data-driven, and student-centered environments. Through qualitative analysis of recent academic studies, this paper examines the integration of AI technologies such as adaptive learning platforms, intelligent tutoring systems, automated assessment tools, and learning analytics. The research highlights that AI enhances individualized learning experiences by tailoring educational content to students' needs, supporting both autonomous and collaborative learning. Furthermore, AI contributes to reducing teacher workload by automating repetitive tasks such as grading and plagiarism detection, thereby allowing educators to focus on creative and critical aspects of teaching. However, the paper also discusses potential challenges, including ethical concerns, data privacy, dependency on technology, and digital inequality. The findings suggest that while AI offers significant advantages, its implementation must be approached with careful planning, ethical consideration, and proper teacher training. This study concludes that the future of higher education lies in the balanced integration of AI tools, where technology enhances – rather than replaces – human pedagogy.